2006
DOI: 10.1007/s00268-005-7959-x
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Fold Paralysis as a Sign of Chest Diseases: A 15‐year Retrospective Study

Abstract: In the diagnosis of VFP due to chest diseases, chest x-ray was useful but not always enough for detecting the primary lesion. Necessity of further examinations including contrast-enhanced chest CT must be kept in mind for the cases with negative chest radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 6 publications
3
25
0
1
Order By: Relevance
“…Chest radiograph remains a useful screening study, but, it is not sufficient for the full evaluation of VCP 11. Because it is very important to scrutinize the mediastinum, particularly the aortopulmonary window and the paratracheal region in patients with VCP,2 further diagnostic imaging may be needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chest radiograph remains a useful screening study, but, it is not sufficient for the full evaluation of VCP 11. Because it is very important to scrutinize the mediastinum, particularly the aortopulmonary window and the paratracheal region in patients with VCP,2 further diagnostic imaging may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes the only sign of an underlying disease 2. Thus, it is clinically important to diagnose the primary disease in cases of vocal cord paralysis (VCP) because many of its potential causes, such as symptom-free malignant tumors, can be fatal or cause serious morbidity if detected late 2,3. Radiologic evaluation is often useful for determining the etiology of VCP, especially for conditions within the thoracic cavity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…46 Recent literature has suggested that some of these cases may, in fact, be caused by diseases affecting the proximal region of the RLN. 2 Several such cases have been published in recent years further elucidating the link between UVP and aortic or pulmonary artery aneurysm, enlarged atrium, or neoplasm affecting the lower lobe of the left lung. 8,16,34,65 Thus, some proportion of those previously diagnosed with idiopathic UVP may have impaired RLN function due to excessive stretch or compression of the nerve associated with changes in the aortic arch, pulmonary vein, or atrium.…”
Section: Introductionmentioning
confidence: 99%